Determination of Vitamin C (Ascorbic Acid) Contents in Two Varieties of Melon Fruits (Cucumis melo L.) by Iodometric Titration - Evana Evana; Maria Selviana Barek (Jurnal Kimia Fullerene, 2021)
Vitamin C, also known as ascorbic acid, is a water-soluble vitamin that is regarded as one of the safest and most effective nutrients. Vitamin C can be found in most fruits, and one of the fruits that contain vitamin C is melon fruit. The objective of the study is to determine vitamin C content in two varieties of melon fruits (Sky Rocket and Rock Melon) through the iodometric titration method. The method of determination was cheap, accurate, and can be used for routine analysis. The samples were collected from different markets in Yogyakarta. The results recorded the concentrations of ascorbic acids in Sky Rocket melon (30.84±0.3066 mg/100 g), and Rock Melon (33.77±0.2237 mg/100 g). The color of the fruit flesh affects the difference in vitamin C content between two varieties of melon fruit. The vitamin C content of orange-colored flesh (Rock Melon) is greater than that of greenish-yellow flesh (Sky Rocket).